New Nickel and Copper Complexes With Thiacalix[4]Arene Derivative Synthesis, Characterization and Catalytic Activity - Al-Khafaji, Yahya; Alalwani, Thamer (Physical Sciences, Life Science and Engineering, 2025)
The study investigates the synthesis and characterization of p-tert-butylthiacalix[4]arene derivative via interaction between p-tert-butylthiacalix[4]arene with two equivalent of 1-bromopropyl to form di-substituted thiacalix[4]arene ring. It is employed to prepare complexes with Ni(II) and Cu(II). The ligand and it is complexes were characterized using elemental analysis, infrared and proton nuclear resonance. Polymerization of cyclic esters was assisted via prepared complexes. The result shows capability of these compounds as catalyst for such reaction.